Colaboração crítica na formação de formadores: pensando possibilidades - Pellossi, Daniela Baccheschi Pioli (2023)
This research focused on analyzing whether and how critical collaboration among researchers takes place during the planning meetings of a class for the course entitled “Engaged Multiliteracy: curriculum as (trans)formation”, carried out by the research group Language in Activity in School Contexts (LACE), hosted at Pontifical Catholic University of São Paulo. The following theoretical contributions support the research: critical teacher education (FREIRE, 1996; MAGALHÃES, 2014; LIBERALI and FUGA, 2014), group formation (SHAW, 1971; MARTIN-BARÓ, 1999, 2017) and critical collaboration (MAGALHÃES, 2011, 2014; NININ and MAGALHÃES, 2017). Theoretically and methodologically, the research is supported by the critical collaborative research (PCCol) (FIDALGO and MAGALHÃES, 2007; MAGALHÃES, 2010, 2011), which aims at the intentional transformation of the contexts of all researchers and participants involved. The analyzed data – three planning meetings and the second class of the course – were collected from video recordings via the Zoom platform, in the year 2021. Data were also produced from: (i) a questionnaire with the researchers involved in the course, in order to investigate their perception of critical collaboration in these meetings and (ii) an unstructured conversation to understand how their participation in the planning and the LACE research group reverberate in their professional practice. The analysis and interpretation of data are supported by Multimodal Argumentation (LIBERALI, 2018b), which integrates Argumentation (LIBERALI, 2018a) and Multimodality (KRESS, 2000, 2010; VAN LEEUWEN, 2005; KRESS and VAN LEEUWEN, 2006). The results point to the engagement of the group of researchers in a critical-collaborative form of work, but there is, at times, a comfortable collaboration (HARGREAVES, 2003). Furthermore, we observed that the occurrence of collaboration and conflicts are perceived by GP LACE researchers as opportunities that favor their personal and professional development, in their pursuit of becoming more responsible and responsive citizens, agents of social transformation (VIANA and STETSENKO, 2011)